The effect of using an enrichment program according to the mathematical correlations in the sports culture of distinguished female students (Journal of the College of Basic Education, 2022)
The present research aims to identify the effect of Enrichment program in accordance with the mathematical correlations in Mathematical Literacy of Distinguished Students , the sample research consists of (63) female students of the first grade intermediate secondary kawther for outstanding women of directorate of Education Baghdad / karkh third /for the academic year (2015-2016). If selected Division (a) by (33) students to represent the experimental group were selected Division (b) by (30) students to represent the control group after the two groups equalized in the variables (age, previous achievement, prior knowledge, intelligence), as the researcher Constructing program Enrichment according mathematical correlations, also prepared scale the mathematical Literacy consists of (45) items part (the first and the second), has been making sure validity and reliability, and then it is applied on the two group search then use (t-test) for data processing, results search showed: There is a statistically significant difference at the level of significance(0.05) between the mean scores of students of the experiment group who are studying according to the Enrichment program and the mean scores of the control group who are studying according to the traditional method in scale the mathematical Literacy, For the benefit of students in the experimental group.